Analisis Debit Aliran dan Muka Air Tanah pada Lahan Gambut Kebun Kelapa Sawit Rakyat di Kabupaten Kubu Raya - Suryadi, Urai Edi (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2023)
Development studies on peatlands relate to the issue of peat restoration with the 3R program, namely rewetting, revegetation and revitalization. This research has a long-term objective in the form of a model of the relationship between water flow discharge and water table depth in peatlands planted with oil palm. The research location is in the Kuala Dua Village area, Sei Raya District, Kubu Raya Regency, which is an area of peatland planted with community oil palm. The research method is a field survey with a grid system. The research implementation consists of determining the location and observation point, installing equipment, measuring the elevation of the observation point in the channel and on the ground surface, measuring the depth of the peat, and measuring the water level in the channel and groundwater level at the observation point, taking soil samples, measuring soil water content. field, Eh, and pH. Measurement of soil hydraulic conductivity at the observation point using the auger hole method. The research results show that the correlation between water flow discharge and water table depth in peat soil is moderate to very strong. The correlation between the rate of decrease in water level and the flow of water in peat soil is very strong. The reductive-oxidative atmosphere of the peat soil layer influences the maturity level, unit weight, total porosity, field water content, field capacity water content, oxidation-reduction potential (Eh), and soil reaction (pH).